The Role of Competition in the Weak Finnish Productivity Growth after the Global Financial Crisis - Lassi, Auri (My University, 2022)
In Finland, the slowdown in labour productivity growth after the global financial crisis has been more severe than in other countries. In economic literature, weak market competition has been linked to lower productivity, as competition encourages firms to innovate and intensifies ‘creative destruction’, which in turn are the primary sources of productivity growth according to Schumpeterian endogenous growth theory. This master’s thesis aims to examine whether there has been any change in the state of competition in the private sector which could have contributed to the slowdown in productivity growth in Finland after the global financial crisis. In the empirical part of this thesis, this is done by investigating several indicators of competition, both static and dynamic, analysing them in absolute terms and in relation to the benchmark group, and finally by comparing the changes in the state of competition to the changes in labour productivity growth at the time and after the global financial crisis. The analysis was carried out utilizing micro-level data from OECD MultiProd and DynEmp databases, and the observation period is from 2004 to 2018. In the light of the indicators analysed and presented in this thesis, the changes in the state of competition do not appear to be the answer to the sluggish productivity growth in Finland after the global financial crisis. In general, there are no noticeable changes in the state of the competition after the global financial crisis. In the observation period, Finland has had a lower productivity dispersion and lower firm mark-ups than in the benchmark, which would actually indicate a fairly good state of competition. There appear not to be any significant problems with business dynamics either. On the contrary, the survival and growth of micro-entrants are higher than in the benchmark. On the other hand, many industries are more concentrated in Finland than in the benchmark, and the allocative efficiency is lower than in the benchmark. However, even these indicators do not show significant changes for worse after the financial crisis, and both indicators have remained stable throughout the observation period.

Työn tuottavuuden kasvu on ollut Suomessa heikompaa kuin muissa maissa globaalin finanssikriisin jälkeen. Heikko kilpailu markkinoilla on taloustieteellisessä kirjallisuudessa yhdistetty matalampaan tuottavuuteen, sillä kilpailu kannustaa yrityksiä innovoimaan ja kiihdyttää ’luovaa tuhoa’, jotka puolestaan ovat Schumpeterin endogeenisen kasvuteorian mukaan ensisijaisia tuottavuuskasvun lähteitä. Tämän pro gradu -tutkielman tavoitteena on tutkia, onko yksityisellä sektorilla tapahtunut muutoksia kilpailutilanteessa, jotka olisivat vaikuttaneet Suomen hidastuneeseen tuottavuuskasvuun finanssikriisin jälkeen. Tutkielman empiirisessä osiossa tätä kysymystä tarkastellaan analysoimalla useita staattisia ja dynaamisia kilpailun mittareita. Mittareita tarkastellaan niin absoluuttisesti kuin myös vertailemalla Suomen arvoja vertailumaajoukon keskimääräisiin arvoihin. Lopulta mittareiden osoittamia mahdollisia kilpailun tilassa tapahtuneita muutoksia verrataan finanssikriisin aikana ja sen jälkeen tapahtuneisiin työn tuottavuuden muutoksiin. Tutkielmassa käytettävä mikrotason data on peräisin OECD:n MultiProd ja DynEmp tietokannoista, ja havaintojaksona on vuodet 2004–2018. Tutkielmassa tarkasteltujen kilpailun mittareiden perusteella kilpailutilanteessa tapahtuneet muutokset eivät vaikuta olleen syynä Suomen heikompaan tuottavuuskasvuun finanssikriisin jälkeen. Yleisesti ottaen, markkinoiden kilpailutilanteessa ei ole tapahtunut huomattavaa muutosta finanssikriisin jälkeen. Suomessa on havaintojaksolla ollut vertailumaajoukkoa matalampi tuottavuuden hajonta ja matalammat yritysten katteet, mikä viittaisi oikeastaan melko hyvään kilpailutilanteeseen. Myöskään yritysdynamiikassa ei vaikuta olevan merkittäviä ongelmia, vaan päinvastoin, markkinoille tulevien mikroyritysten selviytyminen ja kasvu ovat vertailumaajoukkoa korkeammalla tasolla. Toisaalta markkinat ovat Suomessa monella alalla keskittyneemmät, ja allokaatio tehokkuus on matalampi kuin vertailumaajoukossa. Näissäkään mittareissa ei kuitenkaan huomata tapahtuneen merkittävää muutosta huonompaan suuntaan finanssikriisin jälkeen, vaan kumpikin mittari on pysynyt tasaisena koko havaintojakson ajan.
Keywords: productivity, competition, indicators of competition, micro-level data